Adverse Drug Reactions in Polypharmacy Among Elderly Patients: A Clinical Pharmacology Perspective - Usmanovna, Begnaeva Mukhiba (American Journal of Biomedicine and Pharmacy, 2025)
Elderly patients are particularly vulnerable to adverse drug reactions (ADRs) due to age-related physiological changes and the common practice of polypharmacy in managing multiple chronic conditions. This study aims to identify the prevalence, risk factors, and clinical patterns of ADRs among elderly patients exposed to polypharmacy, as well as evaluate the clinical pharmacology principles behind safer prescribing practices. A prospective observational study involving 300 hospitalized elderly patients aged 65 years and older was conducted. Results showed that 39% of patients experienced at least one ADR, with central nervous system agents and cardiovascular drugs being the most implicated. Polypharmacy (≥5 medications), renal impairment, and history of prior ADRs were significant predictors. Rational pharmacological approaches, including medication review, deprescribing, and individualized dosing based on renal and hepatic function, are essential in minimizing ADRs in this population.